2007
DOI: 10.1016/j.sab.2007.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Using of a microcapillary refractive X-ray lens for focusing and imaging

Abstract: The microcapillary lens, formed by air bubbles in a hollow core glass capillary filled with epoxy, is a novel design of a compound refractive lens for X-rays. The epoxy enclosed between two air bubbles has the form of a biconcave lens and acts as a positive lens for X-rays. Each individual lens is spherical with radius of curvature equal to the inner radius of the capillary. Up to 500 individual biconcave lenses can be formed in a single capillary with diameters from 50 to 500 μm. Due to the small radius of cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…The microscope consists of the microfocus X-ray tube, X-ray lens and CCD camera. In contrast to results, described previously in [12][13][14] , here we put X-ray tube far away from the lens. In this case the images of X-ray source and of the object may be found at a different distanced to the lens as it is shown in Fig.…”
Section: X-ray Microscopy With Refractive Lensmentioning
confidence: 95%
See 1 more Smart Citation
“…The microscope consists of the microfocus X-ray tube, X-ray lens and CCD camera. In contrast to results, described previously in [12][13][14] , here we put X-ray tube far away from the lens. In this case the images of X-ray source and of the object may be found at a different distanced to the lens as it is shown in Fig.…”
Section: X-ray Microscopy With Refractive Lensmentioning
confidence: 95%
“…Previously it also was shown that the lenses due to its short focal length are suitable for imaging experiments with conventional X-ray tube as a source of radiation [12][13][14] .…”
Section: Introductionmentioning
confidence: 99%
“…The imaging system (microscope) was designed in the Institute of Applied Physics Problems of Belarus State University (Dudchik et al, 2007b;Dudchik et al 2007c). The system photo is shown in Fig.…”
Section: Energy Kev 12 12mentioning
confidence: 99%
“…The first CRLs were lines of cylindrical holes drilled into aluminum blocks [ 3 ], where the small refractions of individual holes were compounded to achieve a substantial focusing effect [ 3 ]. Since this initial demonstration, CRL technology has been further developed through different designs, including parabolic [ 4 ], spherical [ 5 ], and kinoform [ 6 ] CRLs. Low-attenuation materials such as Al [ 3 ], Be [ 7 ], Si [ 8 ], C [ 9 ] and polymers[ 10 ][ 5 ] together with different fabrication techniques [ 11 ], have been explored.…”
Section: Introductionmentioning
confidence: 99%